OPTIMIZATION OF THE PERFORMANCE OF THE SANDSTONE CRUSHING PLANT UNIT AT PT PULAU LEMON - Kusdarini, Esthi; Ayunida Sasti, Sylvesiana; Shinthya Sari, Avellyn (KURVATEK, 2024)
The process of processing sandstone material at the PT Pulau Lemon crushing unit is not yet optimal. This is due to differences in the amount of material entering and leaving the crushing unit. To optimize the performance of the processing unit, it is necessary to conduct research on the causes of material loss. Furthermore, the research aims to: 1) calculate material loss; 2) assess the causes of material loss and determine efforts to minimize material loss. The research was carried out using mathematical calculations using mass balance equations for material entering and leaving the processing unit, field observations and interviews. The research results showed that the amount of incoming material was 16.66 tons/day and outgoing material was 14.85 tons/day, so the material lost was 1.81 tons/day. or 10.80%. Material loss is caused by the slope of the conveyor belt being less than gentle and some parts being torn, wind, rain and mechanical problems. Efforts to optimize the performance of processing units include reducing waiting times, regularly checking and repairing equipment, and installing roofs.